A single-molecule conformation modulating crystalline polymorph of a physical π–π pyrene dimer: blue and green emissions of a pyrene excimer. Issue 10 (5th February 2020) - Jiang, Wenzhe; Shen, Yue; Ge, Yunpeng; Zhou, Changjiang; Wen, Yating; Liu, Haichao; Liu, Hui; Zhang, Shitong; Lu, Ping; Yang, Bing
Abstract : Blue fluorescence and green fluorescence were observed in two crystals with different pyrene dimers, which are modulated by the molecular conformation. Abstract : Herein, we report a new pyrene (PY)-based derivative, 1-(4-(phenylsulfonyl)phenyl)pyrene (1-DPS-PY), whose two crystals (crystal-B and crystal-G) exhibit sky-blue and green excimer fluorescence, respectively. Crystal-B and crystal-G have a similar dimeric π–π PY stacking in the crystals, but with a different single-molecule conformation. The experimental and theoretical investigations demonstrate that the substituent orientation of 4-(phenylsulfonyl)phenyl (DPS) plays a crucial role in modulating the excited-state properties of the PY excimer. The small twist angle ( Φ ) between DPS and PY facilitates the larger overlap between two PY planes in the excited state, resulting in more red-shifted excimer emission, and vice versa . Moreover, crystal-B shows a photoluminescence (PL) efficiency ( η PL ) as high as 77% due to the better discreteness of PY dimer stacking, in contrast to η PL = 60% of crystal-G with the non-discrete PY dimer stacking. Organic light-emitting diodes (OLEDs) were fabricated with doped and non-doped device structures. The devices showed a gradual emission change from deep blue to sky blue with increasing doping concentration, corresponding to the emission species transformation from a monomer to an excimer. A non-doped device exhibited the best performance with an external quantum efficiency (EQE) of nearly 4.5% and a maximum luminance of 13 733 cd m −2 . These results provide us with a new understanding of the mechanism of the PY excimer, and a new strategy to design the polymorphic PY dimers for high-efficiency excimer fluorescence with tunable emission color.